2022
DOI: 10.1177/10564926221103484
|View full text |Cite
|
Sign up to set email alerts
|

It's a Different World: A Dialog on the Attention-Based View in a Post-Chandlerian World

Abstract: In this Dialog, seven scholars consider the theoretical implications and research opportunities a changing environment presents for the Attention-Based View (ABV). With its roots in the 1950s Carnegie School, ABV is expanding and evolving in ways that accommodate the changes in the corporate context characterized by distributed, porous structures of organizational networks such as ecosystems and platforms. The authors emphasize a shift toward a more dynamic orientation of this research, one that addresses the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 82 publications
1
35
0
Order By: Relevance
“…In this essay, I assume a context containing at least moderate levels of ambiguity that leave more room for emotional influences. This assumption is consistent with the observation that "ambiguity is at the core of organizational decision making and action [in James March's work]" (Ocasio, 2022).…”
Section: Emotions and Emotional Energysupporting
confidence: 85%
“…In this essay, I assume a context containing at least moderate levels of ambiguity that leave more room for emotional influences. This assumption is consistent with the observation that "ambiguity is at the core of organizational decision making and action [in James March's work]" (Ocasio, 2022).…”
Section: Emotions and Emotional Energysupporting
confidence: 85%
“…The dynamic ABV adopted here encourages a less fatalistic perspective on corporate strategists. Consistent with the distributed agency implied by the dynamic ABV (Ocasio et al, 2023), Ericsson's corporate strategists overcame what initially seemed like a radical downgrading. Even in adversity, they were able to bend the pipes of attention at least somewhat to their own advantage.…”
Section: Introductionmentioning
confidence: 88%
“…Given its original emphasis on traditional big businesses, the attention-based view is not particularly well-suited to understand activities that occur beyond organizational boundaries (Ocasio et al, 2022). Crisis research has identified conditions that make crises more likely across operational, managerial, regulatory, and legislative levels-particularly when several such conditions align (e.g.…”
Section: Practices Interface Beyond Organizational Boundariesmentioning
confidence: 99%
“…In fact, all three of its core concepts have undergone substantial transformation. Take the organization: many of the most important organizations today no longer look like traditional big businesses (Ocasio et al, 2022). Organizations are instead more distributed and porous.…”
Section: Introductionmentioning
confidence: 99%